Demonstration of human apolipoprotien A in isolated mucosal cells from small intestine and isolated hepatocytes. Issue 3 (March 1979) - Hopf, U; Assmann, G; Schaefer, H E; Capurso, A
Abstract : Isolated mucosal cells from the human jejunum and stomach, cryostat sections from the jejunum, isolated parenchymal liver cells and lymphocytes were investigated for the presence of apolipoprotien A (apoA). Antisera against purified human apoA-I and apoA-II were raised in rabbits and conjugated with fluorescein-isothiocyanate (FITC). Mucosal cells from jejunum and stomach were isolated with pronase from tissue obtained from operated patients. ApoA-I and apoA-II could be demonstrated in isolated mucosal cells as well as in cryostat sections from the jejunum. The fluorescence pattern in isolated jejunal cells was coarse granular. In the radial gel diffusion test the homogenate from mucosal cells of jejunum showed a single precipitation line with anti-apoA-I and with anti-apoA-II, respectively. The reaction was more intensive with anti-apoA-I than with anti-apoA-II. Isolated gastric cells were negative for apoA. Hepatocytes incubated with FITC anti-apoA-I showed a fine granular fluorescence pattern in the cytoplasm. Anti-apoA-II did not react with hepatocytes. There was no evidence for an in vivo fixation of serum-apoA at the surface of isolated mucosal cells from jejunum or isolated hepatocytes. The results support the hypotheses that in man apoA is synthesised in the epithelial cells of the small intestine and in parenchymal liver cells.